The 1918 Influenza Pandemic: Looking Back, Looking Forward. Issue 12 (20th October 2018) - Viboud, Cécile; Lessler, Justin
Abstract: In commemoration of the centennial of the 1918 influenza pandemic, the American Journal of Epidemiology has convened a collection of 12 articles that further illuminate the epidemiology of that pandemic and consider whether we would be more prepared if an equally deadly influenza virus were to emerge again. In the present commentary, we place these 12 articles in the context of a growing body of work on the archeo-epidemiology of past pandemics, the socioeconomic and geographic drivers of influenza mortality and natality impact, and renewed interest in immune imprinting mechanisms and the development of novel influenza vaccines. We also highlight persisting mysteries in the origins and severity of the 1918 pandemic and the need to preserve rapidly decaying information that may provide treasure troves for future generations.